Malenkij Robot . Malenky Robot - Markó, Judit M. (MTV - Hungarian Television, 2004)
Verzio FF Submission In 1944, round-up for a “little work” of all the Hungarian citizens of German nationality meant heavy years in Soviet labor camps. Survivors talk about deportation, years of hard labor, abuse and the uncertainty of ever returning home.